2019
DOI: 10.1177/0047287519878520
|View full text |Cite
|
Sign up to set email alerts
|

Be Social! The Impact of Self-Presentation on Peer-to-Peer Accommodation Revenue

Abstract: Online peer-to-peer platforms empower individual users and facilitate value-oriented exchanges. Personal profiles are the main point of contact with consumers on these platforms. Although individual sellers can use these profiles to market their own products, the optimal communication strategies that maximize their revenues remain uncertain. In line with construal-level theory, a self-presentation strategy that reduces social distance might increase sellers’ revenues. An empirical validation, based on 6,074 Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 99 publications
0
25
0
Order By: Relevance
“…Chen and Xie (2017) The basic functionality as accommodation is the deterministic factor of consumer evaluation, and social interaction is secondary to functionality in determining consumer valuation of Airbnb listings. García et al (2019) Improving expectations about the guest-host relationship creates a social bond between the guest and the host before the experience. Guttentag et al (2018) Interactivity is identified as a motivating factor to stay at an Airbnb accommodation.…”
Section: Jang Et Al (2019)mentioning
confidence: 99%
See 1 more Smart Citation
“…Chen and Xie (2017) The basic functionality as accommodation is the deterministic factor of consumer evaluation, and social interaction is secondary to functionality in determining consumer valuation of Airbnb listings. García et al (2019) Improving expectations about the guest-host relationship creates a social bond between the guest and the host before the experience. Guttentag et al (2018) Interactivity is identified as a motivating factor to stay at an Airbnb accommodation.…”
Section: Jang Et Al (2019)mentioning
confidence: 99%
“…Social relationships and a sense of community are what visitors seek in an Airbnb accommodation unlike what they look for from traditional hotels (Tussyadiah and Zach 2017). A recent study also describes that enriching the social bond between Airbnb hosts and potential guests could potentially create memorable experiences and boost their revenues, a recommendation that is applicable to other peer-to-peer platforms that involve interactions of seller and consumer such as car-and mealsharing sites (García et al 2019). Living in a residence allows guests to have a more "local" experience by living more like a local resident, interacting with the host or neighbors, and possibly staying in a "nontouristy" area, because Airbnb accommodations are often more scattered than traditional accommodations (Guttentag 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to the social exchange theory (Cropanzano et al, 2017), people exchange social and material resources as a form of social interaction. The social benefits of P2P exchanges are particularly salient in the P2P accommodation domain (Ert et al, 2016;Nieto-García et al, 2019;Tussyadiah, 2016). P2P platforms facilitate social interaction by the sharing of common spaces (e.g.…”
Section: Social Interactionmentioning
confidence: 99%
“…In other words, individuals are likely to present themselves in online settings more easily and freely, because relationship risks are low in online communication compared to those in real-life settings [28]. A recent study also suggests that self-presentation can be a powerful personal branding tool that affects consumer decision-making [29]. Therefore, an individual's desire to present themself can explain their motivation to participate in an online social space and, through this explanation, the relationship between motivation to use social media and a desire for self-presentation can be indirectly understood.…”
Section: Psychological Predictor: Self-presentationmentioning
confidence: 99%